Pengaruh Reward Dan Punishment Terhadap Kinerja Karyawan PT. Multi Garmenjaya - Lestari, Sari; Murdani, Denny (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
The application of Reward and Punishment in the company must be given correctly, it can affect employee performance. The purpose of this study is to see how the Effect of Reward and Punishment on Employee Performance of PT. Multi Garmenjaya. This type of research uses quantitative methods, with distributing questionnaires as many as 93 respondents selected as the population of the study through simple random sampling and producing 93 replies respondents. The results of research ii, namely in thet test, Reward has a tcount value of 5.969 and a ttable value of 1.986 with a Sig value. 0.001 < 0.05 means that Reward has a partial effect on employee performance.Punishment variable has a tcount value of 3.030 and a ttable value of 1.986 with a Sig value. 0.003 <0.05 means that punishment has a partial effect on employee performance. Based on the F test, the Fcount value of 21.440 is greater than the ftabel of 3.10. Because the value of Fhitung > Ftabel (21.440 > 3.10) then H0 is rejected and H3 is accepted, H3 is accepted. This means that the Reward and Punishment variables affect employee performance simultaneously with the coefficient of determination. 0,308 %.